2022
DOI: 10.3390/diagnostics12123026
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Photodynamic Therapy in the Bacterial Decontamination of Periodontal Pockets and Its Impact on the Patient

Abstract: Research in the field of periodontal disease continues to focus on disease-associated microorganisms, as the microbial plaque and the host immune responses are considered to be important causative factors, that are highly responsible for the progression of this disease. The purpose of this article is to compare the reduction in the number of specific periodontopathogens in two test groups according to different therapeutic approaches in periodontal disease and to show possible differences. This article is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Park et al [ 82 ] demonstrated the feasibility of toluidine blue O (TBO)-mediated PDT as a noninvasive supplementary method for the treatment of periodontitis. Many bacteria, including certain oral microbes, can be inactivated by PDT, according to some in vitro investigations [ 83 , 84 , 85 , 86 ]. Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Prevotella intermedia , and Streptococcus sanguis , all of which have been linked to periodontal disease, were demonstrated to be strongly inhibited by aPDT under a variety of settings [ 87 ].…”
Section: Dental Therapeutic Strategiesmentioning
confidence: 99%
“…Park et al [ 82 ] demonstrated the feasibility of toluidine blue O (TBO)-mediated PDT as a noninvasive supplementary method for the treatment of periodontitis. Many bacteria, including certain oral microbes, can be inactivated by PDT, according to some in vitro investigations [ 83 , 84 , 85 , 86 ]. Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Prevotella intermedia , and Streptococcus sanguis , all of which have been linked to periodontal disease, were demonstrated to be strongly inhibited by aPDT under a variety of settings [ 87 ].…”
Section: Dental Therapeutic Strategiesmentioning
confidence: 99%
“…Periodontitis is triggered by a shift in the oral microbiome towards a community enriched in anaerobic Gram-negative bacteria ( Munteanu et al, 2022 ). These microorganisms are equipped with intrinsic virulence factors, including endotoxin and LPS, which is the main constituent of the Gram-negative bacterial outer membrane.…”
Section: Oxidative Stress and Periodontitismentioning
confidence: 99%
“…Currently, experimental and clinical studies on the treatment of purulent wounds and purulent septic complications of the ENT organs using PDT are being carried out [ 12 , 13 ]. The potential use of PDT in dentistry has also been shown [ 14 , 15 ]. Furthermore, antibacterial PDT is a promising technology for the treatment of chronic infections [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%